Products With High Purchase Frequency Require Greater Inhibitory Control: An Event-Related Potential Study - Tsuji, Koki; Shibata, Midori; Terasawa, Yuri; Umeda, Satoshi (Frontiers in Psychology, 2021)
One’s past behavior influences their present behavior. The effects of such response history have often been tested with response inhibition tasks. Since previous studies have highlighted the effect of immediate action history formed directly before the subsequent response in a laboratory environment, we aimed to elucidate the longer-term effects of response history, using repetitive and habitual consumer behavior in daily life as the response history. We used event-related potentials recorded in the Go/No-go task to investigate brain activity related to inhibitory control, hypothesizing that stimuli with a high frequency of choice in everyday life would elicit stronger inhibition-related activity, that is, the No-go-N2 component. In the present study, participants were asked to evaluate the frequency of purchase and use of some products such as food and drink or social networking services in everyday situations. Images of each product were assigned as stimuli in the Go and No-go trials according to the frequency of choice. The results showed that frequently purchased No-go stimuli yielded a larger amplitude of the No-go-N2 component and a negative shift between 200 and 300 ms after the presentation of No-go stimuli. The results suggest that frequently chosen products evoke stronger inhibition conflicts and require greater cognitive control in order to withhold a response. Our findings showed that repeated purchase behavior in daily life forms a response history and has a long-term influence on the inhibition of even simple approaching behaviors such as button pressing.